PRIMARY SCHOOL STUDENTS TRAINING MOVEMENT GAMES IN PHYSICAL EDUCATION CLASSES: PRIMARY SCHOOL STUDENTS TRAINING MOVEMENT GAMES IN PHYSICAL EDUCATION CLASSES - Hasanov, anvar (Физическое воспитание, спорт и здоровье, 2022)
: this article discusses the factors of teaching movement games to students in physical education classes in primary school, a comprehensive approach to the development of students' personality, which helps to develop physical abilities, motor skills and abilities in students.